(Post-)materialist attitudes and the mix of capital and labour taxation - Tobias König; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2008)
Social values shape policy outcomes. We examine the role of postmaterialism, a widely used concept in the social sciences, for the mix of capital and labour taxation chosen by a society. Following political scientist Inglehart, we define the degree of postmaterialism as the relative importance which individuals or a society as a whole ascribe to non-material values over material things. We incorporate this notion into a simple tax model for a small open economy. We show that a greater emphasis on immaterial values will lower the ratio of capital to labour taxes. Subsequently, we test our theoretical results empirically, using a panel data set comprising 17 OECD countries over the period 1981-2000. Proxies for the degree of postmaterialism are developed from the World Values Surveys. Their impact on the tax mix is highly significant and goes into the theoretically predicted direction.
Keywords: Z13; E62; H20; 330; Culture economics; social values; postmaterialism; taxation; Steuerpolitik; Kapitalertragsteuer; Lohnsteuer; Soziale Werte; Postmaterialismus; OECD-Staaten